The development and reliability of an updated dance-specific Star Excursion Balance Test protocol - Beckman, S.; Brouner, J. (Journal of Dance Medicine & Science, 2024)
Background While the previous research has made crucial developments in a dance-specific version of the SEBT, current modifications to the SEBT have not conclusively produced a valid dance-specific dynamic balance test.